Affekt Macht Netz Auf dem Weg zu einer Sozialtheorie der Digitalen Gesellschaft - Mühlhoff, Rainer; Breljak, Anja; Slaby, Jan (Digitale Gesellschaft, 2019)
Shit storms, hate speech or viral videos that promote clicking, linking, sharing: The linked society is driven by affects. The contributions included in this book examine the media-technological developments of our times and explore them from the perspective of a critical affect and social philosophy. They indicate that social media and digital platforms are not only spaces of exchange but also create affect economies - and therein lies their power. By creating new modalities of social interaction and therefore by determining the forms of articulation, they also change the political topography. Including a contribution by Antonio Negri.